A comparative study of ebooks and traditional books in Malaysia - Ramli, Abd Rasyid; Mohd Saad, Shakirah; Md Zani, Rosliza (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2024)
The debate between eBooks and traditional books continues to grow, especially in Malaysia where digital technology adoption is rapidly increasing. This comparative study examines the current trends, advantages, and disadvantages of both formats within the Malaysian context, considering consumer preferences, environmental impacts, and future trends. Research indicates a notable rise in the adoption of digital reading platforms among university students in Malaysia, driven by factors such as convenience and accessibility (Rahim et al., 2021). This trend highlights the broader digital transformation occurring within the country's educational sector.